Which’s more Powerful Digital Power in Papua: Internet Shutdown or Internet Throttling? - Jonah Silas; Caroline Paskarina; Ari Ganjar Herdiansyah (Journal of Governance, 2024)
This research explores the deliberate implementation of internet restrictions by the Indonesian government, focusing on situations of political instability or conflicts that challenge its authority in the digital sphere. The concept of digital power, signifying government control over information in the digital space, is examined, particularly when this control faces challenges leading to internet shutdowns. The study highlights the connection between internet shutdowns and conflict situations, with a specific focus on Papua, indicating the government's use of these measures to suppress potential counterpower. The government's influence over both government and non-government entities, including internet service providers, is emphasized, revealing its ability to enforce internet shutdowns in response to perceived threats to national stability. Despite the positive role of social networking sites in democratic development, uncontrolled information dissemination is viewed as a potential threat, prompting strategic internet shutdowns to maintain narrative control during critical periods.